The effect of carbon sources on the expression level of thermostable L2 lipase in Pichia pastoris - Shahidan, Noor Hidayah; Raja Abdul Rahman, Raja Noor Zaliha; Leow, Adam Thean Chor; Mohamad, Rosfarizan; Basri, Mahiran; Salleh, Abu Bakar (Academic Journals, 2011)
Thermostable lipases are enzymes that are particularly pleasing for industrial purposes such as in the production of detergents, animal skin-based industry and food processing endeavours. Thermostable L2 lipase gene fished out from Bacillus sp. L2 was cloned into Pichia pastoris strain GS115 under constitutive expression system of pGAPZαA. Study performed on various carbon sources revealed that glucose and glycerol support the growth of Pichia pastoris and expression of L2 lipase. In addition, the by-product of sugar refinery processes (molasses) was found to be a potential carbon source for the growth of P. pastoris and L2 lipase expression. Since the thermostable L2 lipase will be extracellularly secreted into the medium, the use of P. pastoris expression system is seen as an alternative to the conventional expression system of Escherichia coli that applies intracellular expression of the L2 lipase gene encoded.